The management of Elementary School's Library (A SiteStudy at SD Kemirirejo 3 Magelang City) - Juriah, Siti (2011)
The Objectives of this study are to describe (1) the class setting of Elementary School library at SD Kemirirejo 3 Magelang City; (2) the library service at SD Kemirirejo 3 Magelang City; (3) the visitor activity of Elementary School Library at SD Kemirirejo 3 Magelang City. It is a qualitative research. This research is conducted at SD Kemirirejo 3 Magelang City. The resource persons in this research are the principal, librarian, teacher and students. Data collection method is depth interview, observation, and documentation. Data analysis used is analysis technique in a site. Data validity uses triangulation. The results of this study show: (1) the setting room service given by the library related to library location, building condition, interior design, lighting of the room is supported with the facility for the library users. In the lobby there is a nursery goods cabinet, bulletin board and exhibit, guest chair, table and chair officer. In the room there are tables and chairs circulation, train books, file cabinets, drawers cupboard user card, computer and shelves that are used by officers. Inside the collection room, there are some bookshelves that are used to store books and reference in the library. In the reading room there is a table read for users of 20 pieces with 40 chairs; (2) services that exist in the library include (a) reference service which is realized by the provision of book and reference in accordance with user need, (b) service locker, namely in the form of nursery goods service for the user, (c) circulation service namely service connected with borrowing and returning book to use an open system and closed system and using the automation system, (d) The librarian or the manager is assisted by a small librarian namely the student selected by the school and library manager, (3) The library service user is governed by the manager through a given schedule in accordance with the effective time in the school. The library user activity includes borrowing and returning book, reading, teaching and learning activity and finishing task. One of the activities carried out in the library is teaching and learning activity undertaken by teacher using multimedia equipment such as LCD projector available in the library. The use of the library as a place of teaching and learning process is not scheduled specifically because it is tailored with the need and depending on the subject teacher or classroom teacher concerned. The use of multimedia equipment in libraries is routinely used for MOS activity for new students.